5
$\begingroup$

The question is that we have to find the real value(s) of $x\in[-1,1]$ satisfying the equation: $${11 \choose 1}x^{10}-{11 \choose 3}x^{8}+{11 \choose 5}x^{6}-{11 \choose 7}x^{4}+{11 \choose 9}x^{2}-{11 \choose 11}=0$$

I couldn't spot any standard series to simplify the expression on the LHS and so I tried writing it as $$\frac{-1}{2}\big[(1+x)^{11}+(1-x)^{11}]$$ but this is obviously not true since it does provide us with the required terms but their signs are not correct.

How can I make the appropriate signs appear on the terms too? I suspect that $i$ may be involved but I'm unsure about how to apply this idea. Any help would be appreciated.

$\endgroup$
1
  • $\begingroup$ You have just obtained the right thing. Just write your 'easier form' like this, $\frac{-1}{2}[(ix+1)^{11}+(ix-1)^{11}]$. Now, this will be $0$ when $\frac{(ix+11)}{(ix+11)}=(-1){\zeta_{11}}^k ,k\leq11$ where, $\zeta_{11}$ is $11$ th root of unity. $\endgroup$
    – Alapan Das
    May 2, 2020 at 14:53

2 Answers 2

3
$\begingroup$

Hint:

$$\dfrac{(1+y)^{2n+1}+(1-y)^{2n+1}}2=\sum_{r=0}^{r\le n}\binom{2n+1}{2r}y^{2r}$$

We have $$\sum_{r=0}^n\binom{2n+1}{2r}(-1)^rx^{2r}=0$$

Comparing $y=ix$

So, $$(1+ix)^{2n+1}=-(1+ix)^{2n+1}$$

$$\iff\left(\dfrac{1+ix}{1-ix}\right)^{2n+1}=-1=e^{(2m+1)i\pi}$$

$\endgroup$
1
3
$\begingroup$

Perhaps this will help:

$$(x+i)^{11}={11\choose 0}x^{11}+{11\choose 1}x^{10}i -{11\choose 2}x^{9}- {11\choose 3}x^{8}i+...$$

and

$$(x-i)^{11}={11\choose 0}x^{11}-{11\choose 1}x^{10}i -{11\choose 2}x^{9}+ {11\choose 3}x^{8}i+...$$

so your expresion is:$$ i\cdot {(x+i)^{11} -(x-i)^{11}\over 2}$$

$\endgroup$
1
  • $\begingroup$ Shouldn't it be $\frac{i}{2}$ on the outside? $\endgroup$ May 2, 2020 at 14:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.